2015
DOI: 10.1038/srep08958
|View full text |Cite
|
Sign up to set email alerts
|

Maskless milling of diamond by a focused oxygen ion beam

Abstract: Recent advances in focused ion beam technology have enabled high-resolution, maskless nanofabrication using light ions. Studies with light ions to date have, however, focused on milling of materials where sub-surface ion beam damage does not inhibit device performance. Here we report on maskless milling of single crystal diamond using a focused beam of oxygen ions. Material quality is assessed by Raman and luminescence analysis, and reveals that the damage layer generated by oxygen ions can be removed by non-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…A similar mechanism is also evoked here, to explain the intermixing of F e and Si atoms and the crystallization into the B20 and D0 3 phases of F eSi and F e 3 Si, respectively. In all these experiments carbon removal is induced by an electron-beam-mediated reaction of carbon with residual gas molecules, like H 2 O and O 2 , present in the microscope chamber [31].…”
Section: Discussionmentioning
confidence: 99%
“…A similar mechanism is also evoked here, to explain the intermixing of F e and Si atoms and the crystallization into the B20 and D0 3 phases of F eSi and F e 3 Si, respectively. In all these experiments carbon removal is induced by an electron-beam-mediated reaction of carbon with residual gas molecules, like H 2 O and O 2 , present in the microscope chamber [31].…”
Section: Discussionmentioning
confidence: 99%
“…As the quantum emission usually originates from point defects in wide bandgap materials, it is extremely important that processing steps would not introduce any additional defects or quench the emitting sites. Past studies demonstrated that H 2 O-mediated FEBIE is a highly suitable technique to directly pattern diamonds [73][74][75] and hexagonal boron nitride [76] -materials that host most promising point defects for single photon emitters (Figure 4).…”
Section: Electron Beam-induced Processesmentioning
confidence: 99%
“…To achieve the full potential of high‐mobility 2D semiconductors in integrated optoelectronics networks and multipixel readout digital circuits, the prerequisite lies in accurate and efficient patterning of the 2D materials into designed architectures and integrated modules . To this end, great efforts have been devoted to developing effective dry‐etch approaches for patterning with excellent controllability, such as exemplified by focused ion beam etching, femtosecond laser etching, and reactive ion etching . In contrast to these relatively expensive and complicated dry etching techniques, wet chemical etching is a desirable way for its prominent advantages such as simple procedure, scalable production, well controllability, and low cost .…”
mentioning
confidence: 99%